The Francisella Type VI Secretion System - Clemens, Daniel L.; Lee, Bai-Yu; Horwitz, Marcus A. (Frontiers in Cellular and Infection Microbiology, 2018)
Francisella tularensisis subsp. tularensis is an intracellular bacterial pathogen and the causative agent of the life-threatening zoonotic disease tularemia. The Francisella Pathogenicity Island encodes a large secretion apparatus, known as a Type VI Secretion System (T6SS), which is essential for Francisella to escape from its phagosome and multiply within host macrophages and to cause disease in animals. The T6SS, found in one-quarter of Gram-negative bacteria including many highly pathogenic ones, is a recently discovered secretion system that is not yet fully understood. Nevertheless, there have been remarkable advances in our understanding of the structure, composition, and function of T6SSs of several bacteria in the past few years. The system operates like an inside-out headless contractile phage that is anchored to the bacterial membrane via a baseplate and membrane complex. The system injects effector molecules across the inner and outer bacterial membrane and into host prokaryotic or eukaryotic targets to kill, intoxicate, or in the case of Francisella, hijack the target cell. Recent advances include an atomic model of the contractile sheath, insights into the mechanics of sheath contraction, the composition of the baseplate and membrane complex, the process of assembly of the apparatus, and identification of numerous effector molecules and activities. While Francisella T6SS appears to be an outlier among T6SSs, with limited or no sequence homology with other systems, its structure and organization are strikingly similar to other systems. Nevertheless, we have only scratched the surface in uncovering the mysteries of the Francisella T6SS, and there are numerous questions that remain to be answered.